Exnovatie: duurzame transities in Brussel anders voorstellen - Ela Callorda Fossati; Solène Sureau; Bonno Pel; Tom Bauler; Wouter Achten (Brussels Studies, 2022)
With the concept of exnovation, Sustainability Transitions (ST) studies are experiencing a paradigm shift. Their typical focus on sustainable niche innovations has now shifted to shed light on the reverse side of these emergence processes: the exit routes from socio-technical systems which cause problems of unsustainability. This article introduces the exnovation shift which is taking place within STs and illustrates its relevance in understanding the challenges of transition governance in Brussels. Based on a review of the literature and an exploratory analysis, this article discusses the limits of transition strategies based solely on support for niche innovations, presents two emblematic cases which structure the literature on exnovation, and emphasises the need to consider new areas which integrate the challenges of exnovation at city level. Applied to the case of Brussels, the concept of exnovation allows a systemic and critical reading of the challenges facing the Low Emission Zone.